Метод побудови інформаційної технології системи підтримки прийняття рішень для багаторівневих підприємств з сезонною діяльністю - Чикунов, П. О.; Криводубський, О. О. (НТУ "ХПІ", 2014)
Пропонується метод розробки інформаційної технології системи підтримки прийняття рішень підприємства с багаторівневою структурою та сезонним характером формування портфелю заказів. Розглянути питання системного аналізу характеристик діяльності підприємства, розробки логікоформальних моделей, моделей сезонного планування та оперативного управління, функціоналів цілі управління та алгоритму функціонування інформаційної технології.

The work is devoted to solving scientific problems of formation a constructions method of the information technology by decision support system based on systematic analysis of the characteristics of the technical and economic activities in processing enterprise with multi-level management structure and the seasonal nature of the formation and execution of the order book and with multilevel forecasting seasonal and monthly indicators, with polyvariance determination of optimal values loading of capacities and operational management of processing complex. In method are includes: the system analysis of the characteristics of the enterprise, the development of logical-formal models of relationship performance, static mathematical models of seasonal planning, dynamic models of operational management, functional goals of optimal control, numerical procedures for solving equations and finding optimal solutions and an algorithm of information technology. Static statistical models of strategic and tactical planning differs from the existing by subject areas and recurrent adaptation process. Dynamic deterministic real-time model differ from existing by adaptive parameters estimation procedures. An improved method for coordinated interaction of decision-makers in determining the performance of the production program, which consists of a hierarchy of subordination making solutions for different criteria.
The constructions method of the information technology by decision support system for multilevel enterprise with seasonal activities
Keywords: прийняття управлінського рішення; інформаційна технологія; критерії управління; багаторівневі системи управління; алгоритми управління; діяльність підприємства; decision support system; information technology; systems analysis; management criteria; multi-level system management; process modeling; control algorithms